ETNOMATEMATIKA PADA KELENTENG TJOE TIK KIONG PASURUAN SEBAGAI BAHAN PAKET TES SISWA SMP KELAS VIII - Afifudin, Mochammad (Kadikma, 2020)
The purpose of this study was to determine what ethnomatematics in the Tjoe Tik Kiong Temple and produce a test package related to ethnomatematics in the Tjoe Tik Kiong Temple. This temple is a place of worship for the Tri Dharma people in Pasuruan City. This type of research is qualitative research with an ethnographic approach. The subjects of this study were one religious leader and one handyman. Data collection methods used are observation and interviews. In this study focused on several objects of building and carving shapes. Mathematical concepts that emerged in the Tjoe Tik Kiong Temple building were geometric, congruent, similarity and geometric transformation. The product made is a test package related to ethnomatematics at the Tjoe Tik Kiong Temple in Pasuruan. This test package is intended for junior high school grade VIII